INDUSTRIAL REVOLUTION IN “LONDON” BY WILLIAM BLAKE - Rianto, Issabel Mustika Ajeng (LANTERN (Journal on English Language, Culture and Literature), 2016)
This research deals with the situations and conditions happened in England at the end of the seventeenth century. Based on the fact that there is a relation between history and literature, the writer analyzes the history of industrial revolution in England. The aim of this research is to understand the poem of William Blake entitled “London”. The writer also tries to figure out social problems happened in England reflected in the poem.  The writer uses library research as the method of data collection and sociological approach in analyzing the data. By using the library research method, the writer gets many references to write this final project. By using the sociological approach the writer could understand the social context of the poem. The result of this final projectshows that Blake tends to show the impact of industrial revolution and the social condition happened in England through the figurative languages in his poetry.